2001
DOI: 10.1002/1097-0045(20010201)46:2<142::aid-pros1018>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Laminin‐1 and α6β1 integrin regulate acinar morphogenesis of normal and malignant human prostate epithelial cells

Abstract: BACKGROUND. Cell±matrix interactions via integrin receptors are critical for acinar morphogenesis. The non-tumorigenic, human prostate epithelial cell line RWPE-1 was used in a three-dimensional (3D) cell culture model to identify the matrix protein and its integrin receptor required for acinar morphogenesis. METHODS. 3D cultures, immunostaining, confocal microscopy, and Western blot analysis were used to examine acinar formation on matrix proteins and to determine integrin receptor expression. RESULTS. RWPE-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 0 publications
3
34
0
1
Order By: Relevance
“…RWPE-1 cells undergo acinar-like morphogenesis with spherically arranged polarization and both structural and functional differentiation when grown in a 3D Matrigel environment (Bello-DeOcampo et al, 2001b). When RWPE-1 cells were transfected with control GL2-luciferase siRNA, they organized themselves into distinct acini 4 days after plating on Matrigel ( Figure 6A, a), similar to non-transfected cells (data not shown).…”
Section: Dkk-3 In Prostate Cell Growth and Morphogenesis Y Kawano Et Almentioning
confidence: 63%
See 1 more Smart Citation
“…RWPE-1 cells undergo acinar-like morphogenesis with spherically arranged polarization and both structural and functional differentiation when grown in a 3D Matrigel environment (Bello-DeOcampo et al, 2001b). When RWPE-1 cells were transfected with control GL2-luciferase siRNA, they organized themselves into distinct acini 4 days after plating on Matrigel ( Figure 6A, a), similar to non-transfected cells (data not shown).…”
Section: Dkk-3 In Prostate Cell Growth and Morphogenesis Y Kawano Et Almentioning
confidence: 63%
“…Reduction of Dkk-3 expression in RWPE-1 cells resulted in a decrease in acinar size and a failure of acinar formation, suggesting that Dkk-3 is important for acinar development and/or differentiation. There are a number of crucial events necessary for normal acinar formation, including growth factor stimulation (Hoffman et al, 1996;Bello-DeOcampo et al, 2001b), cell-matrix interactions (Hoffman et al, 1996;Bello-DeOcampo et al, 2001a;Naylor et al, 2005) and cell-cell interactions (Hoffman et al, 1996;Menko et al, 2002). Experiments are underway to determine which of these is altered upon depletion of Dkk-3.…”
Section: Discussionmentioning
confidence: 99%
“…Although knockdown of TEAD1 or c-Cbl in RWPE1 did not affect proliferation in 2D culture, the ability of these cells to form acini in an established 3D assay (Bello-DeOcampo et al, 2001;Kawano et al, 2006) was compromised. These data suggest that TEAD1 and c-Cbl could have roles in regulating prostate epithelial cell differentiation and may have additional functions in epithelial morphogenesis, such as regulating adhesion to the basement membrane and associated signalling.…”
Section: Discussionmentioning
confidence: 91%
“…Assays developed to measure neural and mammary stem cell self-renewal in vitro propagate these cells as spheres in an attempt to preserve their specialized biology (23,24). Several studies have shown that human prostate cells can form epithelial spheroids when cocultured with stromal cells and suspended in Matrigel in vitro (25)(26)(27). This strategy was adapted to develop a method for measuring murine prostate stem cell self-renewal.…”
Section: The Lsc Subpopulation Is Enriched For Sphere-forming Cells Withmentioning
confidence: 99%